2018
DOI: 10.1080/17408989.2018.1485138
|View full text |Cite
|
Sign up to set email alerts
|

How can video feedback be used in physical education to support novice learning in gymnastics? Effects on motor learning, self-assessment and motivation

Abstract: Background: Much of the existing research concerning the use of video feedback (VFB) to enhance motor learning has been undertaken under strictly controlled experimental conditions. Few studies have sought to explore the impact of VFB on the skill learning experience of the students in a structured, school-based physical education (PE) setting. Most of those studies have only used qualitative approaches to implicate the potential value of VFB to enhance skill acquisition, students' engagement or selfassessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 77 publications
3
87
1
14
Order By: Relevance
“…Video recordings of prior trials allow students to monitor, asses and, if necessary, adjust their performances in subsequent trials. Potdevin et al (2018), for example, found that the self-assessment of movement technique combined with video feedback and the supporting verbal instructions of a PE teacher enhanced learning a gymnastic skill in a PE setting and decreased amotivation during the learning program. However, the majority of studies addressing self-regulation and feedback have predominantly been carried out in lab-based situations, instead of during real PE lessons (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Video recordings of prior trials allow students to monitor, asses and, if necessary, adjust their performances in subsequent trials. Potdevin et al (2018), for example, found that the self-assessment of movement technique combined with video feedback and the supporting verbal instructions of a PE teacher enhanced learning a gymnastic skill in a PE setting and decreased amotivation during the learning program. However, the majority of studies addressing self-regulation and feedback have predominantly been carried out in lab-based situations, instead of during real PE lessons (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although the benefits of self-controlled feedback on motor learning seem convincing, at least for laboratory situations, the underlying relationships between self-control, motor learning and motivational beliefs are still debated (e.g. Potdevin et al 2018;Sanli et al 2013;Wulf and Lewthwaite 2016). An influential model that addresses the relationships between self-regulation, motivational beliefs and (motor) learning is Zimmerman's self-regulation of learning model (2000).…”
Section: Introductionmentioning
confidence: 99%
“…The work with the video was done only in separate workshop and individually with each student; it already greatly reduced the anxiety of the students. Potdevin et al (2018) add that video feedback can be used in physical education to support novice learning in gymnastics and motivate students. The fact that the tools were used unambiguously gave students the feeling that the camera was part of the work equipment that helps them progress and they adapt more easily.…”
Section: Analysis Of the Computer Communication Technology (Cct) Funcmentioning
confidence: 99%
“…It seems that the tool is interesting to the point of trying to also perceive the errors to anticipate the regulations of the teacher or the speaker during their verbal corrections. Let's not forget that it is the verbal regulations associated with video feedback that are the source of important motor progressions (Potdevin et al, 2018;Rabardel, 1995). And sometimes, students themselves could correct themselves.…”
Section: Analyzing Effects Of Video Feedbackmentioning
confidence: 99%
“…Current and future pedagogical research is needed to examine ways students can use one of the video feedback (VFB) technologies for better self-regulation, with the potential to provide appropriate movement feedback, based on different levels of experience. in students [1]. Technological advances have led sports pedagogics and physical education teachers to review strategies to provide feedback related to motor learning by students using video feedback [2].…”
Section: Introductionmentioning
confidence: 99%